2006
DOI: 10.1111/j.1525-1470.2006.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Richner–Hanhart Syndrome (Tyrosinemia II): Early Diagnosis of an Incomplete Presentation with Unusual Findings

Abstract: We report a 2-year-old girl with an incomplete form of Richner-Hanhart syndrome (tyrosinemia II) whose presenting sign was the appearance of vesicles on the fingertips. In a few months these lesions evolved into typical hyperkeratotic plaques also involving the palms and soles. Photophobia and frequent tearing were observed but there was no intelligence impairment. Serum and urine tyrosine levels confirmed the diagnosis. A low tyrosine and phenylalanine diet permitted good control of the disease with a complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…These lesions are typically present on both palms and soles except in cases 63 and 114, who only had affected soles, and there was an unusual presentation with vesicular lesions in the fingertips (Id. 110) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These lesions are typically present on both palms and soles except in cases 63 and 114, who only had affected soles, and there was an unusual presentation with vesicular lesions in the fingertips (Id. 110) …”
Section: Resultsmentioning
confidence: 99%
“…110). 38 Only 2 cases presented with severe mental retardation: One patient (Id. 57) had an inherited TAT deletion of 50 kb plus a de novo large chromosomal deletion spanning the TAT locus, who in addition suffers from multiple congenital anomalies, 17,18 while the other patient (Id.…”
Section: Rhs Mutation Update At the Tat Locusmentioning
confidence: 99%
“…Skin lesions consist of painful hyperkeratotic plaques of soles and palms (8,9). The fingertips and the hypothenar and thenar eminences are areas of predilection (10).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the actual concentration that is reached into the brain of type II patients is not known. It was reported that plasma tyrosine levels may exceed 1000 μM in untreated type II patients (Scott, 2006), but other studies found that plasma tyrosine values range from 370 to 3420 μM (Goldsmith et al, 1973; Lemonnier et al, 1979; Rabinowitz et al, 1995; Mitchell et al, 2001; Macsai et al, 2001; Viglizzo et al, 2006). Although some effects presented here may have pathophysiological relevance to tyrosinemia type II, we cannot rule out that these effects were suprapathological.…”
Section: Methodsmentioning
confidence: 99%